Nitric Oxide Acts as an Early Diagnostic Tool for Intrauterine Diseases in Animal Health (Bangladesh Journal of Infectious Diseases, 2024)
Background: Intrauterine pathologies in animals are a significant cause of reduced reproductive performance and symptomatic infertility, leading to economic losses in the livestock industry. Early diagnosis of these conditions is critical for effective treatment and management.Objective: The study aimed to develop a method for the early diagnosis of intrauterine pathologies in animals by assessing nitric oxide (NO) levels using Electron Paramagnetic Resonance (EPR) spectroscopy.Methodology: An experimental model was created using dairy Escherichia coli culture, which was injected into the uterus of pregnant rabbits under ultrasound guidance. Determination of the level of nitric oxide was accessed in the laboratories of the FSSI "Federal Research Center for Chemical Physics named after. N.N. Semenov" Russian Academy of Sciences. The study involved three groups of rabbits: two groups infected either intrauterine or intraperitoneally, and a control group. Group I (Intrauterine Infection) consisted of two rabbits. A suspension of Escherichia coli was injected directly into the uterus through the cervical canal to induce an intrauterine infection. Group II (Intraperitoneal Infection): This group included five rabbits. The Escherichia coli suspension was administered intraperitoneally, serving as a comparative model for systemic infection. Group III (Control): The remaining two rabbits served as the control group. These rabbits were not infected and were used to establish baseline measurements for comparison.Results: The results demonstrated that the concentration of nitric oxide derivatives, specifically nitrites and N-nitrosamines (RNNO), significantly increased in the blood plasma of infected rabbits compared to the control group. These changes were observed during the early stages of inflammation, indicating the onset of intrauterine pathologies.Conclusion: The developed method based on measuring nitric oxide derivatives in blood plasma is effective for the early diagnosis of intrauterine pathologies in animals.Bangladesh Journal of Infectious Diseases, June 2024;11(1):52-58